Exploring Cultural Competence amongst OT Students - Pragashnie Govender; December M. Mpanza; Tarryn Carey; Kwenzile Jiyane; Bicolé Andrews; Sam Mashele (Occupational Therapy International)
Occupational therapy relies primarily on communication between the therapist and client for effective intervention. Adequate communication may be influenced by language and cultural differences between the therapist and client. Cultural competence in relation to language and culture is thus a vital part in practice. Limited research exists on cultural competence in occupational therapy students. This study thus aimed to explore the cultural competence of final year students and their perceptions of their own cultural competence, with respect to language and culture in their practice as students. An explorative qualitative study design was utilised with a nonprobability purposeful sample of 21 final year undergraduate students at a tertiary institute in South Africa. Three focus groups were conducted, comprising between 6 and 8 students in each group. Thematic analysis using inductive reasoning was undertaken in order to analyse the students’ experiences and understanding of cultural competence. Findings of the study suggest that cultural competence, in relation to language and culture, influences the occupational therapy intervention process. It was shown to both positively and negatively influence intervention through supporting or hindering rapport building, client centeredness, and effective intervention.